Historical Muscat : an illustrated guide and gazetteer - Peterson, John, 1947- (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2007)
Historical Muscat is an attempt to define and explain the historical environment that determined the significance and design of Oman's capital city Muscat, its twin city Matrah, and their environs prior to 1970. It also examines how the development of the Muscat conurbation since 1970 has transcended the historical boundaries of the existing settlements and how the process of development has proceeded largely without any consideration of the impact on Muscat's tangible or remembered history. At the heart of the book is a historical gazetteer of forts, gates, palaces, mosques, houses, quarters, settlements, and other sites covering the broader Muscat region from Bandar Jissah to al-Sib. The text is accompanied by a large number of illustrations, including maps from various eras and both historical and more contemporary photographs.